Social things : an introduction to the sociological life - Lemert, Charles C., 1937- (Lanham : Rowman & Littlefield, 1997)
Discusses the practice and nature of sociology, looking at its history, how it developed as an academic discipline, and is uses as a tool to provide people with an understanding of their social environment.
Includes bibliographical references (p. 195-199) and index.
Adult.
Adult
Keywords: Sociology; Sociology -- History; Sociology; Sociology -- History